Flexible Workforce: The Political Economy of the Greek Garment Industry in the Era of Neoliberalism - Canals,Amadeus (2013)
This thesis set out to explain the emergence of production units that favour harsh working conditions in the garment industry of Athens. A neo-Marxist political economic approach was used in order to trace the causes of this emergence over the last fifty years and explain the transitional period from Fordism to flexible regimes of accumulation. The hollowing out of the Welfare State in favour of Neoliberal policies has had several implications for the garment industry and the working conditions of migrant garment workers. A new hierarchical organizational structure has evolved and new strategies have been adopted by manufacturers and retailers. As a consequence, different forms of vulnerability now threaten garment workers. A total of 40 semi structured interviews were conducted with individuals representing various parts of the industry and the state. Last but not least, an attempt was made to illustrate the implications for middle income countries particularly those of Latin America.
Keywords: working conditions; migrant workers; Neoliberalism; flexible accumulation; garment industry; neoliberal fashion